Correction to: Roles of nitric oxide and ethyl pyruvate after peripheral nerve injury - Sandesh Panthi; Kripa Gautam; Junyang Jung (Inflammation and Regeneration, 2019)
After publication of the original article [1], it came to our attention that Professor Junyang Jung was omitted from the authorship.